(untitled) (Bangladesh Agronomy Journal, 2015)
An intercropping experiment was conducted at the Regional Agricultural Research Station, BARI, Ishurdi, Pabna during 2007-2008 and 2008-2009 to find out the suitable intercrop combination for increasing total productivity and returns. Seven treatments, viz. sole pointed gourd, two times lalshak + two rows turmeric in between pointed gourd lines, two times spinach + two rows turmeric in between pointed gourd lines, one time bushbean + two rows turmeric in between pointed gourd lines, two times lalshak + two rows ginger in between pointed gourd lines, two times spinach + two rows ginger in between pointed gourd lines and one time bushbean + two rows ginger in between pointed gourd lines were compared. All the intercropping combinations were higher in terms of pointed gourd equivalent yield, gross return, gross margin and benefit cost ratio (BCR) over sole crops. The highest pointed gourd equivalent yield (105.92 t ha-1) and gross return (Tk. 2118480 ha-1) was found from two times spinach + two rows ginger in between pointed gourd lines combination. The land equivalent ratio was observed highest (2.29) in same combination which was similar to one time bushbean + two rows ginger in between pointed gourd lines combination. One time bushbean + two rows ginger in between pointed gourd lines combination gave the highest monetary returns in respect of gross margin (Tk.1623333 ha-1) and BCR (4.19). The increases in total productivity in terms of pointed gourd equivalent yields were 53.72-128.62 t ha-1 in intercrop combination compared to base crop. Bangladesh Agron. J. 2015, 18(1): 7-12